PENGARUH KESELAMATAN KESEHATAN KERJA (K3) DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PARAGON TECHNOLOGY AND INNOVATION DI TANGERANG - Ahmad Buchtiarrurifai; Lili Sularmi (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of occupational health safety (K3) and work discipline on employee performance at PT. Paragon Technology and Innovation in Tangerang. The method used is quantitative. The sampling technique used saturated sampling, namely 62 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that occupational health safety (K3) has a significant effect on employee performance with a coefficient of determination value of 44.9% and the hypothesis test obtained t count > t table or (7.732 > 2.000). Work discipline has a significant effect on employee performance with a coefficient of determination value of 39.0% and the hypothesis test obtained t count > t table or (6.194 > 2.000). Occupational health safety (K3) and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 10.217 + 0.421X1 + 0.336X2. The coefficient of determination value is 60.2% while the remaining 39.8% is influenced by other factors. Hypothesis testing obtained a calculated F value > F table or (44.626 > 2.760).